Is poverty or wealth driving HIV transmission? - Gillespie, Stuart; Kadiyala, Suneetha; Greener, Robert (Ovid Technologies, 2007)
Evidence of associations between socioeconomic status and the spread of HIV in different settings and at various stages of the epidemic is still rudimentary. Few existing studies are able to track incidence and to control effectively for potentially confounding factors. This paper reviews the findings of recent studies... in an attempt to uncover the degree to which, and the pathways through which, wealth or poverty is driving transmission in sub-Saharan Africa. We investigate the question of whether the epidemic is transitioning from an early phase in which wealth was a primary driver, to one in which poverty is increasingly implicated. The paper concludes by demonstrating the complexity and context-specificity of associations and the critical influence of certain contextual factors such as location, gender and age asymmetries, the mobility of individuals, and the social ecology of HIV transmission.